Analisis Pengendalian Kualitas Produk Tahu Menggunakan Metode Six Sigma di UMKM Tahu Prapto - Kharin Nugeraha; Andung Jati Nugroho (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
Data reveals that at UMKM Tahu Prapto, out of 9,450 tofu products produced, 1,016 products were defective, indicating quality control issues in August 2024. By implementing the six sigma method, it is expected to identify defects to determine the company's sigma value, so that the company can improve its sigma value to compete in the market and provide improvement recommendations aimed at reducing the existing product defects in Tahu. In its implementation, six sigma has 5 (five) steps to improve business performance, namely define, measure, analyze, improve, and control, so that problems or opportunities, processes, and customer requirements must be verified and updated at each step. Further analysis using the Pareto diagram identifies specific defects in the tofu product, such as dirty tofu, incorrect size, unpleasant texture, and bad odor. The proposed improvements include scheduling regular equipment cleaning, ensuring the maintenance and cleanliness of production machines, and maintaining a clean working environment to prevent contamination of tofu products